Effects of biocontrol agents on some soybean pathogens, diseases and yields - X.B. YANG, SHRISHAIL S. NAVI*, A.H. RAJASAB and (Indian Phytopathology, 2016)
Species of Trichoderma, Coniothyrium and Talaromyces biocontrol agents (BCA) have significantly (P<0.05) affected growth and reproduction of Fusarium virguliforme (FV) and Rhizoctonia solani (RS). Also, Trichoderma spp. significantly mycoparasitised both FV and RS in dual culture plates within a week of incubation. Based on in vitro results, untreated Pioneer 22T61R soybean seed was treated with individual spore suspension of the BCA (5-ml/kg) followed by bioAPT microbial carrier powder (1g/kg). Treatments with water and bioAPT served as controls-1 and 2 respectively. Seeds and inocula were planted using ALMACO 4-Row SeedPro Precision Vacuum planter with an automatic cable winding trip system. In soybean sudden death syndrome (FV) plots, significant (P<0.05) differences in stand count, and disease index was observed among BCA+bioAPT and over controls. Also, yield advantages in BCA + bioAPT plots varied from 0.09 to 0.41 Mt/ha over control-1 and 0.11 to 0.56 MT/ha over control-2. Whereas, in Rhizoctonia root rot (RS), some BCA+bioAPT plots showed significant (P<0.05) differences in stand counts, and disease incidence (%). Similar to SDS there was 0.01Â-0.59 Mt/ha yield increase over control-2. In both the trials, bioAPT supported BCA in improving yields.